2022
DOI: 10.3389/fped.2022.946547
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Successful Treatment of a Child With COVID-19 Reinfection-Induced Fulminant Myocarditis by Cytokine-Adsorbing oXiris® Hemofilter Continuous Veno-Venous Hemofiltration and Extracorporeal Membrane Oxygenation

Abstract: BackgroundIndirect cardiomyocyte damage-related hyperinflammatory response is one of the key mechanisms in COVID-19-induced fulminant myocarditis. In addition to the clinical benefit of using cytokines absorption hemofiltration, the effectiveness of instituting veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support for cardiac compromise has been reported. However, current literature enunciates a paucity of available data on the effectiveness of these novel modalities.Case PresentationWe reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This study is the first to report on the use of oXiris© in children with vasoplegic shock. Phan et al [17] reported on a 9-year-old child treated with a combination of VA-ECMO and oXiris© for fulminant myocarditis related to COVID-19. Pediatric patients treated with other devices for blood purification or with conventional CRRT are largely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to report on the use of oXiris© in children with vasoplegic shock. Phan et al [17] reported on a 9-year-old child treated with a combination of VA-ECMO and oXiris© for fulminant myocarditis related to COVID-19. Pediatric patients treated with other devices for blood purification or with conventional CRRT are largely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of thrombocyte count was not constantly described in the literature. Schwidenhammer et al [15] did not report a thrombocyte count reduction, while others reported a significant decrease over time [17, 20, 27]. However, the real clinical impact of such reduction is unknown in the absence of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with viral pathogens, such as influenza and parvovirus B-19, has been widely described as the most common etiology of acute myocarditis, but less is known about cardiac complications of SARS-CoV-2 infection. While myocardial problems associated with SARS-CoV-2 have been well reported in adults, few cases of pediatric COVID-19-related acute myocarditis have been reported to date (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). We collected twelve such case reports, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…IVIGs are commonly used to treat inflammatory diseases with cardiac involvement due to their immune-modulating activity. CVVH may limit further cardiotoxicity from possible indirect damage in fulminant hypercytokinemia-associated SARS-CoV-2 ( 15 ). Remdesivir, a direct-acting nucleotide prodrug inhibitor of the SARS-CoV-2 RNA-dependent RNA polymerase, may shorten the recovery time in patients hospitalized with COVID-19 and was associated with fewer days of subsequent oxygen use in patients receiving oxygen and shorter subsequent duration of mechanical ventilation or ECMO ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation